2021
DOI: 10.12775/jehs.2021.11.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of illness and quality of life in patients with type 2 diabetes

Abstract: Background: results of studies concerning the quality of life in chronic diseases and the predictors thereof are a source of valuable information making it possible to take the right actions, both educational, at every stage, and therapeutic. The assessment acceptance of illness and the quality of life enables the identification of patients' actual problems and objections as well as the recognition of their needs for the purpose of treatment optimization.Objective: The aim of the study was to evaluate the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Acceptance of the illness has a significant effect on the therapeutic process of the patients [36] who suffer from chronically the disease throughout their entire lives; therefore, their approach to their illness is particularly important. Based on the results obtained in the current study, it can be concluded that the higher the level of acceptance of the illness, the higher the level of the QoL in all its domains.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of the illness has a significant effect on the therapeutic process of the patients [36] who suffer from chronically the disease throughout their entire lives; therefore, their approach to their illness is particularly important. Based on the results obtained in the current study, it can be concluded that the higher the level of acceptance of the illness, the higher the level of the QoL in all its domains.…”
Section: Discussionmentioning
confidence: 99%
“…According to the scale total score mean; it can be said that "the acceptance of illness of the individuals is mild levels". In former studies, it has been reported that individuals with TIIDM have low or mild acceptance of their illnesses (Bak et al, 2017;Besen & Esen, 2012;Can et al, 2020;Krzemińska & Kostka, 2021;Olszak et al, 2016;Rogon et al, 2017;Starczewska et al, 2018;Şahin & Cingil, 2020;Şireci & Karabulutlu, 2017;Yılmaz et al, 2019). Individuals with TIIDM emphasized that living with diabetes is a difficult process.…”
Section: Discussionmentioning
confidence: 99%